Benefits and burdens of newborn screening: public understanding and decision-making. (August 2014) - Nicholls, Stuart G; Wilson, Brenda J; Etchegary, Holly; Brehaut, Jamie C; Potter, Beth K; Hayeems, Robin; Chakraborty, Pranesh; Milburn, Jennifer; Pullman, Daryl; Turner, Lesley; Carroll, June C
In this article we review the literature regarding the public understanding of the potential benefits and burdens of expanded newborn bloodspot screening. We draw attention to broadened notions of benefit that go beyond early identification of asymptomatic individuals and interventions to reduce morbidity or mortality, and include benefits gained by families through knowledge that may facilitate life choices, as well as gains generated by avoiding diagnostic delays. We also reflect on burdens such as increasing false-positive results and parental anxiety, together with risks of overdiagnosis when the natural history of a condition is poorly understood. We conclude that expanded notions of benefit and burden bring with them implications for parental consent and confidentiality and the secondary use of bloodspots.